VD_FINDINFO Jug / 2012 / 184 vom 28. März 2012 - VD Tribunal cantonal (2012)
VIOL, ACTE D'ORDRE SEXUEL AVEC UN ENFANT, CONTRAINTEDROIT PÉNAL, PRESSION, FIXATION DE LA PEINE | 187 ch. 1 al. 1 CP, 190 al. 1 CP, 47 CP